Floristic, ecological and ethnobotanical aspects of Mammillaria deherdtiana subsp. dodsonii (Cactaceae), an endemic and threatened plant - Rendón-Aguilar, Beatriz; Bernal-Ramírez, Luis Alberto; Arias-Montes, Ángel Salvador; Jiménez-Sierra, Cecilia Leonor; Ballesteros-Barrera , Claudia; Ortega-Jiménez, Sinuhé; Bravo-Avilez, David (Instituto de Ecología, A.C., 2022)
Background and Aims: In Oaxaca, Mexico, 26 species of the genus Mammillaria are reported, seven of them being endemic. Mammillaria deherdtiana subsp. dodsonii is listed as threatened. The objectives of this paper were to describe the demographic, reproductive and ethnobotanical aspects of its use, as well as the floristic and bioclimatic aspects of the studied localities.Methods: In January 2015, two localities of Mammillaria deherdtiana subsp. dodsonii were found in the Sierra Norte. Between January and March, five transects of 5 m2 were located in one of them, in which the number of individuals was recorded, size categories were established, and the population structure was obtained. For the flowering process, ten flowers were chosen, and the perianth diameter was recorded every two hours. The vascular plants surrounding the sampled site were recorded and data on climatic variables were obtained. The inhabitants were interviewed to document the local knowledge and uses of this cactus.Key results: The population structure is multimodal. Juvenile individuals make up 65% and reproductive adults 33% in the studied locality. Anthesis lasts seven hours; dichogamy and hercogamy were observed, indicating a xenogamous breeding system. The subspecies is recognized with names in Spanish and Zapotec and is occasionally used as food, medicine, and ornament. Fifteen species belonging to the Pinus and Abies forest were recorded. The environmental preferences of the subspecies are temperatures of 9.6-12.7 °C, and precipitation of 1009-1405 mm.Conclusions: The xenogamous breeding system is worrisome due to the observation of just one floral visitor. The presence of bristles and radial spines in this subspecies suggests morphophysiological adaptations to cold. It is advisable to delve into the presence and effectiveness of pollinators and the recruitment dynamics of the subspecies.